2013
DOI: 10.1111/emip.12014
|View full text |Cite
|
Sign up to set email alerts
|

Using State Assessments for Predicting Student Success in Dual‐Enrollment College Classes

Abstract: Scores on state standards‐based assessments are readily available and may be an appropriate alternative to traditional placement tests for assigning or accepting students into particular courses. Many community colleges do not require test scores for admissions purposes but do require some kind of placement scores for first‐year English and math courses. In this study, we examine the efficacy of using the reading and math portions of the Kansas State Assessment (KSA) for predicting the success of high school s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Kingston and Anderson (2013) found the Kansas State Assessment Reading scores were not as strong of a predictor of performance in college classes as the Math Kansas State Assessment. The findings from Kingston and Anderson (2013) differ from the findings of Kitsantas et al (2008), who found the SAT verbal was the strongest predictor of performance between the SAT math and SAT verbal assessments.…”
Section: Cognitive Factorsmentioning
confidence: 74%
See 4 more Smart Citations
“…Kingston and Anderson (2013) found the Kansas State Assessment Reading scores were not as strong of a predictor of performance in college classes as the Math Kansas State Assessment. The findings from Kingston and Anderson (2013) differ from the findings of Kitsantas et al (2008), who found the SAT verbal was the strongest predictor of performance between the SAT math and SAT verbal assessments.…”
Section: Cognitive Factorsmentioning
confidence: 74%
“…Similar studies in Washington, Connecticut, Arizona, and Massachusetts all found state assessments predicted performance in college courses as well as the SAT and ACT assessments (Cimetta et al, 2010; Nichols-Barrer et al, 2020). Kingston and Anderson (2013) found the Kansas State Assessment Reading scores were not as strong of a predictor of performance in college classes as the Math Kansas State Assessment. The findings from Kingston and Anderson (2013) differ from the findings of Kitsantas et al (2008), who found the SAT verbal was the strongest predictor of performance between the SAT math and SAT verbal assessments.…”
Section: Review Of Literaturementioning
confidence: 74%
See 3 more Smart Citations